1999
DOI: 10.1523/jneurosci.19-16-06955.1999
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Neuronal Caspase-3 by Intracellular Accumulation of Wild-Type Alzheimer Amyloid Precursor Protein

Abstract: Forced overexpression of wild-type Alzheimer amyloid precursor protein (APP) causes postmitotic neurons to degenerate. Caspase-3 (CPP32) is a principal cell death protease involved in neuronal apoptosis during physiological development and under pathological conditions. Here, we investigated whether APP overexpression activates caspase-3 in human postmitotic neurons using adenovirus-mediated gene transfer. When a recombinant adenovirus vector expressing human wild-type APP695 was infected in vitro into neurall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 44 publications
4
67
1
Order By: Relevance
“…11 The present study has shown that APPDC31 induced caspase-3-independent neuronal death. These findings suggested that APPDC31 induces apoptosis in a manner distinct from that of wild-type APP.…”
Section: Cytotoxicity Of Appdc31 Is Not Specific To Postmitotic Neuronssupporting
confidence: 52%
See 3 more Smart Citations
“…11 The present study has shown that APPDC31 induced caspase-3-independent neuronal death. These findings suggested that APPDC31 induces apoptosis in a manner distinct from that of wild-type APP.…”
Section: Cytotoxicity Of Appdc31 Is Not Specific To Postmitotic Neuronssupporting
confidence: 52%
“…21,22 Furthermore, tau, a microtubule-associated protein whose abnormal phosphorylation is thought to cause formation of neurofibrillary tangles seen in AD, is cleaved by caspase-3 in vitro, and overexpression of the caspase-cleaved N-terminal fragment of tau induces apoptosis of NT2 stem cells and COS cells. 23,24 These Neuronal specificity of caspase-mediated apoptosis induced by wild-type APP Overexpression of wild-type APP causes caspase-3-mediated apoptosis of postmitotic neurons but not of nonneuronal cells, 11 suggesting that a neuron-specific machinery is involved in APP-induced caspase-3 activation. It has been demonstrated that two adaptor proteins, mammalian Disabled and FE65, which are primarily expressed in neurons, interact with the cytoplasmic tail of APP that contains the adaptor protein-binding motif NPTY.…”
Section: Caspase-3-independent Apoptosis Induced By Appdc31mentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of both APP and Tau mRNA are elevated in Down's syndrome (Oyama et al, 1993). It was suggested that the C-terminal fragments of APP, 676 -695, is possibly essential along with Tau to PHF formation (Caputo et al, 1992) and increased level of APP induces activation of caspase (Uetsuki et al, 1999), implying a role of APP in ⌬Tau-induced cell death. Thus far, while a number of putative tauopathies have been identified, the pathological mechanism is not fully understood.…”
Section: Discussionmentioning
confidence: 99%